2017
DOI: 10.12659/msm.906003
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Predictors of Mortality After Mitral Valve Surgery in High-Risk Elderly Patients: The Heidelberg Experience

Abstract: BackgroundOverall, life expectancy at the age of 80 has significantly increased in the industrialized world and the proportion of this age class undergoing cardiac surgery has also grown. In this context, we have analyzed a contemporary series of octogenarians undergoing mitral valve surgery at our institution.Material/MethodsWe performed a retrospective analysis of 138 consecutive octogenarians receiving mitral valve surgery between January 2006 and April 2017. Preoperative comorbidities, early mortality, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
2
8
1
2
Order By: Relevance
“…Emergency/salvage surgery was found to be an independent predictor of 30-day mortality, similar to other study results [10,11,7]. The pathologies that mandate emergency valve surgery, including acute mitral incompetence following acute myocardial infarction or acute valve incompetence secondary to infective endocarditis, put the patient in a state of acute HF, increasing the risk of death.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Emergency/salvage surgery was found to be an independent predictor of 30-day mortality, similar to other study results [10,11,7]. The pathologies that mandate emergency valve surgery, including acute mitral incompetence following acute myocardial infarction or acute valve incompetence secondary to infective endocarditis, put the patient in a state of acute HF, increasing the risk of death.…”
supporting
confidence: 87%
“…Older patients have multiple comorbidities with deterioration of organ function. In patients > 80 years old, emergency surgery and CABG were the most important predictors of early mortality after mitral valve surgery (both repair and replacement), with estimated mortality of 18% [10]. Similarly, in patients undergoing AVR, emergency surgery, atrial brillation, and older age were the strongest predictors of mortality [11].…”
Section: Discussionmentioning
confidence: 99%
“…16,19 In our study, this group of patients had the highest in hospital mortality rate, that is, 14.3%, and these results are in line with current literature. 20,21 In con trast to our results, Mkalaluh et al 22 determined CABG as the only concomitant procedure that was a predictor of early mortality after MV sur gery. The discrepancy might result from different regarding etiological factor of MR (P = 0.13) ( TABLE 3 and 4).…”
Section: What's Newsupporting
confidence: 57%
“…Furthermore, we classified eti ologies of MR not only on the basis of echocar diographic criteria but also surgical findings. In the Euro Heart Survey study, where surgical patient characteristics, as Mkalaluh et al 22 an alyzed only octogenarians, and patients in our study were much younger. In this study, besides concomitant other valve surgery, other factors associated with higher risk of death were age, severe heart failure symptoms, impaired LVEF, previous percutaneous coro nary interventions, CPB time, LCO, and wound infections.…”
Section: What's Newmentioning
confidence: 57%
“…Chronic obstructive pulmonary disease (COPD) is one of the comorbidities that has been associated with the decision to not operate [9]. However, in a recent study, Mkalaluh et al [10] analyzed a contemporary series of octogenarians undergoing mitral valve surgery at their institution and found that COPD did not influence 30-day mortality.…”
Section: Introductionmentioning
confidence: 99%